(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study presents a corpus-based comparative analysis of the semantic and functional features of etiquette lexis in written English and Uzbek. Focusing on common polite expressions – greetings, farewells, thanks, apologies, requests, and honorifics – the analysis draws on large text corpora and existing literature to uncover how each language encodes politeness. The results show that both English and Uzbek employ conventionalized formulas to fulfill similar social functions, yet cultural values shape their usage in distinctive ways. English written etiquette tends toward brevity and indirectness, reflecting an emphasis on individualism and negative politeness (minimizing imposition). In contrast, Uzbek etiquette lexis is often more elaborate and expressive, reflecting the language’s collectivist orientation and respect-based norms. Uzbek writings frequently incorporate honorifics, kinship terms, and even blessings as part of polite expressions, underscoring the importance of hierarchy and sincerity in Uzbek culture. Similarities were observed in the core functions of etiquette expressions (e.g. maintaining social harmony), but differences abound in form, frequency, and context of use. These findings highlight how deeply cultural and social factors are embedded in language use. By understanding the comparative pragmatics of English and Uzbek politeness formulas, linguists and language learners can better appreciate the interplay between language, culture, and society in shaping courteous communication.